Perencanaan dan Pelaksanaan Pendidikan Kecakapan Hidup di SMP - Sri Wahyuni; Made Pidarta (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2004)
This study was conducted to investigate the planning and implementation of life-skill education at SMP Negeri 2 Selong, East Lombok. In this descriptive study, the researcher’s role was both as a subject and as the main instrument. The data were obtained from in-depth interviews, observation, and documentation. The results revealed that the planning of life-skill education was strategically and operationally running well through the school vision, mission, and programs. The implementation of life-skill education consisted of personal skills or self awareness, thinking skills, social skills, academic skills and vocational skills which were integrated in the teaching learning process and in all the school activities. Life-skill education, which cannot be separated from the three aspects of education (cognition, affection and psychomotor), enabled the students to prepare themselves for possible life problems and to solve them.